2020
DOI: 10.1021/acs.iecr.9b06058
|View full text |Cite
|
Sign up to set email alerts
|

New Approach for Catalytic Production of Ultralow-Sulfur Diesel Fuels Using Binary Composed Catalysts Consisting of Cobalt Nanoparticles

Abstract: The global trend is orientated toward the production of diesel fuels composed of as low as 50 ppm (0.05 g/L) or even less sulfur compounds. As a result, the current study is orientated toward the generation of a diesel fuel with reduced sulfur content via the catalytic route. This research work introduces novel approaches in the catalytic desulfurization field through providing new perspectives. A special attention has been paid throughout this research toward the usage of advanced catalytic compositions in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This increase in weight loss could be attributed to the release of hydrazine particles that might be attached within the structure of both Ni and carbon during the preparation procedures. 34,35…”
Section: Resultsmentioning
confidence: 99%
“…This increase in weight loss could be attributed to the release of hydrazine particles that might be attached within the structure of both Ni and carbon during the preparation procedures. 34,35…”
Section: Resultsmentioning
confidence: 99%
“…The main concept of this process is the removal of organosulfur compounds in presence of hydrogen gas and catalyst at high temperature and pressure where sulfur is converted to H 2 S (Bataille et al 2000, Lecrenay et al 1997, Topsøe et al 1996.This technique suffers from certain drawbacks concerning the operating costs, the limitation of sulfur compounds removal, especially the refractory compounds, and the rapid deactivation of employed catalysts. In 2020, El Naggar and co-workers had reported new advances in such a technique through reducing operational costs and conservation of the catalyst lifetime (El Naggar et al 2020). Nevertheless, HDS has become a globally unfavorable methodology due to the extensive emissions of H 2 S gas.…”
Section: Introductionmentioning
confidence: 99%
“…KIT‐6 has a high surface area per volume ratio, high hydrothermal stability, large and tunable cylindrical pores with high interconnectivity and thick walls 31 . KIT‐6 has advantages over one‐dimensional and two‐dimensional mesoporous structures due to its ordered three‐dimensional pore structure with two intertwined systems of mesoporous channels providing more active sites for functionalization, more resistance to pore blocking, and more permeability without sacrificing the selectivity 32 . It has been shown that the addition of KIT‐6 to the polymeric matrix enables the fabrication of intimate composites due to the penetration of polymer chains into the relatively large pores of the mesoporous 33 .…”
Section: Introductionmentioning
confidence: 99%
“…31 KIT-6 has advantages over one-dimensional and two-dimensional mesoporous structures due to its ordered three-dimensional pore structure with two intertwined systems of mesoporous channels providing more active sites for functionalization, more resistance to pore blocking, and more permeability without sacrificing the selectivity. 32 It has been shown that the addition of KIT-6 to the polymeric matrix enables the fabrication of intimate composites due to the penetration of polymer chains into the relatively large pores of the mesoporous. 33 However, so far, there are no reports on the rejection of heavy metal ions by the KIT-6 incorporated nanocomposite membrane.…”
mentioning
confidence: 99%